Upaya Hukum Grasi Di Dalam Pelaksanaan Pemidanaan Di Indonesia - Cayo, Putri Sari Nilam (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Abstract Based on the records of various International Human Rights Institutions, Indonesia is one of the countries that still applies the death penalty to their criminal law system (Retentionist Country). The legal research method used is a normative juridical research type. The legal force of court decisions and the existence of clemency for the execution of sentences in Indonesia can be stated that court decisions that have obtained permanent legal force in the form of punishment in any form cannot be cancelled and are given decisions by government power outside the scope of the judiciary. Although there is already a judicial review (herziening) that can be used by convicts, pardons that are outside the realm of law and outside the criminal justice system can be used by the president as a means to correct and demonstrate legal wisdom. Keywords: Law, Clemency, Convict